You are on page 1of 11

124 Chapter 18 Simple Techniques of Integration

CHAPTER 18 9. ∫ cos 2 xdx = 2 sin 2 x + C


1

Exercise 18A (p.192)


∫ sin( 7 )dx = −7 cos( 7 ) + C
x x
10.

∫ ( x + 6)
1
1. 7
dx = ( x + 6 )8 + C
8
∫ cos(4 x − 7)dx = 4 sin(4 x − 7) + C
1
11.
3 +1
(8 x − 1) (8 x − 1)
4
∫ (8x − 1) dx = +C = +C
3
2.
8(3 + 1) 32
∫ sin( 9 − 7)dx = −9 cos( 9 − 7) + C
x x
12.

∫ ( x + 2) 4 = ∫ ( x + 2)
dx −4
3. dx

∫ sin(−
6x 5 6x
( x + 2) −3 13. + 8)dx = cos( − + 8) + C
= +C 5 6 5
−3
1
= − ( x + 2) −3 + C 5 − 4x 5 − 4x
∫ cos(
3
3 14. )dx = − sin( )+C
3 4 3

∫ (1 − x )3 dx = 4∫ (1 − x )
4 −3
∫ (sin 3x + cos 4 )dx = ∫ sin 3xdx + ∫ cos 4 dx
4. dx x x
15.

4(1 − x ) −2 1 x
= − cos 3 x + 4 sin + C
= +C 3 4
( −1)( −2)
= 2(1 − x ) −2 + C
∫ (2 sin 2 − 3 cos 2 x )dx
x
16.

∫ ∫
dx
= (2 x − 3) − 2 dx
1

= 2 ∫ sin dx − 3∫ cos 2 xdx


5. x
2x − 3 2
1
(2 x − 3) 2 x 3
= +C = −4 cos − sin 2 x + C
2( 12 ) 2 2
= 2x − 3 + C
x 2 − 6 x + 11 ( x − 3)2 + 2
17.
∫ dx = ∫ dx
∫ ∫
1
6. 1 − 2 xdx = (1 − 2 x ) dx 2 x2 − 6x + 9 ( x − 3)2


2
(1 − 2 x ) 2
3
= [1 + ]dx
= +C ( x − 3)2
( −2)( 23 )
= ∫ dx + 2 ∫ ( x − 3) −2 dx
1 3
= − (1 − 2 x ) 2 + C 2
3 =x− +C
x−3

∫ ∫
x x 1
7. 3 − dx = (3 − ) 2 dx
2 2 4x2 − 4x + 9 (1 − 2 x )2 + 8
(3 − 2 ) 2
x 3 18. ∫ (1 − 2 x )2
dx = ∫ (1 − 2 x )2 dx
= 1 3 +C
( − 2 )( 2 ) = ∫ [1 +
8
]dx
4 x 3 (1 − 2 x )2
= − (3 − ) 2 + C
3 2 = ∫ dx + 8∫ (1 − 2 x ) −2 dx
(1 − 2 x ) −1
∫ ∫ = x + 8[ ]+ C
dx
8. = ( x − 1) −3 dx ( −2)( −1)
x − 3x + 3x + 1
3 2

( x − 1) −2
4
=x+ +C
= +C 1 − 2x
−2 4
1 =x− +C
= − ( x − 1) −2 + C 2x − 1
2
Chapter 18 Simple Techniques of Integration 125

3 x (3 x − 2 ) (3 x − 1)2 − 1 ∴ − x 2 + 14 x − 1
19.
∫ (3 x − 1)2
dx = ∫ (3 x − 1)2
dx
= ( A + B) x 2 + (2 A − 2 B) x + A + B
= ∫ [1 − (3 x − 1) −2 ]dx  A + B = −1
2 A − 2 B = 14

= ∫ dx − ∫ (3 x − 1) −2 dx
∴ A = 3 , B = −4
(3 x − 1) −1
=x− +C − x 2 + 14 x − 1
3( −1)
1
(b) ∫ ( x 2 − 1)2
dx
=x+ +C

3(3 x − 1) 3 4
= [ − ]dx
( x − 1) 2
( x + 1)2
12 x + 36 x + 1 3(2 x + 3) − 26 = 3∫ ( x − 1) −2 dx − 4 ∫ ( x + 1) −2 dx
2 2
20.
∫ (2 x + 3)2
dx = ∫ (2 x + 3)2 dx 4 3
= − +C
= ∫ [3 −
26
]dx x +1 x −1
(2 x + 3)2
= 3∫ dx − 26 ∫ (2 x + 3) −2 dx
x +1 A( x − 1)2 B( x − 1) C
−1 24. (a) = + +
(2 x + 3) ( x − 1) 3
( x − 1) 3
( x − 1) 3
( x − 1)3
= 3 x − 26 +C
2( −1) A( x 2 − 2 x + 1) + B( x − 1) + C
13 =
= 3x + +C ( x − 1)3
2x + 3
∴ Ax 2 + ( B − 2 A) x + ( A − B + C ) = x + 1
3 x + 27 x + 81x + 21
3 2
21. ∫ ( x + 3)3
dx 

A=0
 B − 2A = 1
3( x + 3)3 − 60  A − B + C = 1
= ∫ ( x + 3)3
dx
∴ A = 0 , B = 1, C = 2

60
= [3 − ]dx x +1
∫ ( x − 1)3 dx = ∫ ( x − 1)2 + ∫ ( x − 1)3
dx 2 dx
( x + 3)3 (b)
= 3∫ dx − 60 ∫ ( x + 3) −3 dx 1 1
=− − + C1
= 3x +
30
+C x − 1 ( x − 1)2
( x + 3)2 −( x − 1) − 1
= + C1
( x − 1)2
(2 x − 1)2 − 1
∫ 4 x( x − 1)(2 x − 1) ∫ (2 x − 1)2 dx
−2 x
22. dx = =− + C1
( x − 1)2
= ∫ [1 −
1
]dx
(2 x − 1)2
= ∫ dx − ∫ (2 x − 1) −2 dx
Exercise 18B (p.196)

∫ sin 2 x cos 3xdx = 2 ∫ [sin 5x + sin(− x )]dx


1 1
=x+ +C 1.
2(2 x − 1)
1 1
= cos x − cos 5 x + C
− x + 14 x − 1
2 2 10
23. (a)
( x 2 − 1)2
A B
∫ cos 4 x sin 5xdx = 2 ∫ [sin 9 x − sin(− x )]dx
= + 1
2.
( x − 1) 2
( x + 1)2
= ∫ sin 9 xdx + ∫ sin xdx
A( x + 1) + B( x − 1)2
2 1 1
= 2 2
( x − 1)2 ( x + 1)2
1 1
( A + B) x 2 + (2 A − 2 B) x + A + B =− cos 9 x − cos x + C
= 18 2
( x 2 − 1)2
126 Chapter 18 Simple Techniques of Integration


1 1
∫ ∫
1 = sin x ⋅ (1 − cos 4 x )dx
3. sin x sin 3 xdx = (cos 2 x − cos 4 x )dx
2 4 2


1 1 1
= sin 2 x − sin 4 x + C = (sin x − sin x cos 4 x )dx
4 8 8


1 1
= [sin x − (sin 5 x − sin 3 x )]dx
8 2
∫ cos 4 x cos 5xdx = ∫ 2 (cos 9 x + cos x )dx
1 1 1 1
4.
= − cos x − cos 3 x + cos 5 x + C
1 1 8 48 80
= sin 9 x + sin x + C
18 2

∫ sin x cos xdx


4 4
11.
∫ ∫
1
5. cos 3 x cos 2 xdx = (cos 5 x + cos x )dx
= ∫ ( sin 2 x ) 4 dx
2 1
1 1 2
= sin 5 x + sin x + C
= ∫ [ (1 − cos 4 x )]2 dx
10 2 1 1
16 2

64 ∫
1
∫ sin ∫ 2 (1 − cos 4 x )dx
1
6. 2
2 xdx = = (1 − 2 cos 4 x + cos 2 4 x )dx


1 1
= ∫ dx − ∫ cos 4 xdx
1 1
= [1 − 2 cos 4 x + (1 + cos 8 x )]dx
2 2 64 2


x 1 1 3 1
= − sin 4 x + C = ( − 2 cos 4 x + cos 8 x )dx
2 8 64 2 2
3 1 1
= x− sin 4 x + sin 8 x + C
∫ (sin x + cos x ) ∫
128 128 1 024
7. 2
dx = (1 + sin 2 x )dx
1
=x− cos 2 x + C
π
∫ [1 − sin( x + 5 )] dx
2 12. 2

π π
= ∫ [1 − 2 sin( x + ) + sin 2 ( x + )] dx
∫ sin ∫
x cos xdx = sin 2 x sin x cos xdx
8. 3
5 5
π π
= ∫ sin 2 x sin 2 xdx = ∫ {1 − 2 sin( x + ) + [1 − cos 2( x + )]} dx
1 1
2 5 2 5
π π
= ∫ (1 − cos 2 x )sin 2 xdx = ∫ [ − 2 sin( x + ) − cos 2( x + )] dx
1 1 3 1
2 2 2 5 2 5
π
= ∫ (sin 2 x − sin 2 x cos 2 x )dx
1
= ∫ dx − 2 ∫ sin( x + )dx
3
4 2 5
π
= ∫ (sin 2 x − sin 4 x )dx
1 1
− ∫ cos 2( x + )dx
1
4 2 2 5
1 1 3 π 1 π
= − cos 2 x + cos 4 x + C = x + 2 cos( x + ) − sin 2( x + ) + C
8 32 2 5 4 5

∫ sin 2 x cos ∫ 2 sin 4 x cos 2 xdx


1
9. 2
2 xdx =
∫ cos ∫
1
13. 3
xdx = cos x ⋅ (1 + cos 2 x )dx
= ∫ (sin 6 x + sin 2 x )dx
1 1 2


1
2 2 = (cos x + cos x cos 2 x )dx
1 1 2
=− cos 6 x − cos 2 x + C

1 1
24 8 = [cos x + (cos 3 x + cos x )]dx
2 2

∫ sin x cos xdx ∫


3 2 1 3 1
10. = ( cos x + cos 3 x )dx
2 2 2
= ∫ sin x (sin 2 x cos 2 x )dx 3 1
= sin x + sin 3 x + C
4 12
= ∫ sin x ( sin 2 x )2 dx
1
2
Chapter 18 Simple Techniques of Integration 127

∫ sin 4 x cos x cos 3xdx


(b) Applying the definition of indefinite integral to
14.
the result of (a),
= ∫ (sin 5 x + sin 3 x ) cos 3 xdx
1 x n (1 + x ) 2
3

2 3 + 2n
∫ ∫
x n (1 + x ) 2 dx + n x n −1 (1 + x ) 2 dx
1 1
=
= ∫ (sin 5 x cos 3 x + sin 3 x cos 3 x )dx
1
2
2 3 + 2n
= In + nIn −1
= ∫ [ (sin 8 x + sin 2 x ) + sin 6 x ]dx
1 1 1
2
2 2 2 2 3 2n
1 1 1 ∴ In = x n (1 + x ) 2 − In −1
= − cos 2 x − cos 6 x − cos 8 x + C 3 + 2n 3 + 2n
8 24 32

(c) I0 = x 0 1 + xdx =
∫ 1 + xdx

∫ sin ∫
1
15. 4
xdx = [ (1 − cos 2 x )]2 dx =
2 3
(1 + x ) 2 + C
2 3

1
= (1 − 2 cos 2 x + cos 2 2 x )dx I1 =
2 3
x (1 + x ) 2 −
2
I0
4 3+2 3+2

1 1
= [1 − 2 cos 2 x + (1 + cos 4 x )]dx 2 3 4
= x (1 + x ) 2 − (1 + x ) 2 + C1
3

4 2 5 15

1 3 1
= ( − 2 cos 2 x + cos 4 x )dx 2 2
I2 = x (1 + x ) − I1
3
2
4
4 2 2 7 7
3 1 1
= x − sin 2 x + sin 4 x + C 2 2
= x (1 + x ) −
3
2
8 3
x (1 + x ) 2
8 4 32 7 35
16 3
+ (1 + x ) + C2
2

105
Exercise 18C (p.198)
∴ ∫x 1 + xdx = I2
2
d n 1
1. (a) x (1 + x ) 2 2 2 3 8 3 16 3
dx = x (1 + x ) 2 − x (1 + x ) 2 + (1 + x ) 2 + C
1 n 7 35 105
= nx n −1 (1 + x ) 2 + x (1 + x ) − 2
1 1

2
nx n −1 (1 + x ) xn d
= + 3. (a) tan n −1 x = (n − 1) tan n − 2 x (sec 2 x )
1+ x 2 1+ x dx
nx n −1
(2 n + 1) x n = (n − 1) tan n − 2 x (1 + tan 2 x )
= +
1+ x 2 1+ x = (n − 1) tan n x + (n − 1) tan n − 2 x
(b) Applying the definition of indefinite integral (b) Applying the definition of indefinite integral to
to the result of (a), the result of (a),
1
x n (1 + x ) 2 =
nx n −1
∫ dx + ∫
2n + 1 x n
dx ∫ ∫
tan n −1 x = (n − 1) tan n xdx + (n − 1) tan n − 2 xdx
1+ x 2 1+ x
∫ ∫
1
2n + 1 tan n −1 x = tan n xdx + tan n − 2 xdx
= nIn −1 + In n −1
2 1
2 1 tan n −1 x = In + In − 2
∴ In = [ x n (1 + x ) 2 − nIn −1 ] n −1
2n + 1 1
2 2n In = tan n −1 x − In − 2
= xn 1 + x − In −1 n −1
1 + 2n 1 + 2n

(c) I2 = tan 2 xdx

d n 3 = tan x − I0
2. (a) x (1 + x ) 2 = tan x − x + C1
dx
∫ tan xdx = I4
3 4
= nx n −1 (1 + x ) 2 + x n ( )(1 + x ) 2
3 1

2 1
3 n 1
n −1 1 = tan 3 x − I2
= x (1 + x ) + nx (1 + x )(1 + x ) 2
2
3
2 1
3 + 2n n = tan 3 x − tan x + x + C
x (1 + x ) 2 + nx n −1 (1 + x ) 2
1 1
= 3
2
128 Chapter 18 Simple Techniques of Integration

d (c) By the result of (b), for any integer n ≥ 1 ,


4. (a) sec n − 2 θ tan θ
dθ d
cos n x sin nx = (n + n) cos n x cos nx
= sec n − 2 θ sec 2 θ dx
+ (n − 2)sec n −3 θ(sec θ tan θ)(tan θ) − n cos n −1 x cos(n − 1) x
= sec n θ + (n − 2)sec n − 2 θ tan 2 θ
= sec θ + (n − 2)sec
n n−2
θ(sec θ − 1)
2 ∫
cos n x sin nx = 2 n cos n x cos nxdx

= (n − 1)sec n θ − (n − 2)sec n − 2 θ ∫
− n cos n −1 x cos(n − 1) xdx
n −1

2 n cos x cos nxdx = n cos ∫ x cos(n − 1) xdx
(b) Applying the definition of indefinite integral n
to the result of (a),
+ cos x sin nx
n
sec n − 2 θ tan θ
∫ cos ∫
1
cos n −1 x cos(n − 1) xdx
∫ ∫
= (n − 1) sec n θdθ − (n − 2) sec n − 2 θdθ x cos nxdx =
n
2
= (n − 1) J n − (n − 2) J n − 2 1
+ cos n x sin nx
1 n−2 2n
∴ Jn = sec n − 2 θ tan θ + Jn − 2
n −1 n −1 (d) By (c),

∫ ∫ cos x cos 3xdx


3
(c) J2 = sec 2 θdθ = tan θ + C1

= ∫ cos 2 x cos 2 xdx + cos3 x sin 3 x


1 2 1 1
J4 = sec 2 θ tan θ + J2
3 3 2 6
= ( ∫ cos x cos xdx + cos 2 x sin 2 x )
1 2 1 1 1
= sec 2 θ tan θ + tan θ + C2
3 3 2 2 4
1
+ cos3 x sin 3 x
∫ sec 6 θdθ 6


= J6 1 1
= cos 2 xdx + cos 2 x sin 2 x
1 4 4 8
= sec 4 θ tan θ + J 4 1
5 5 + cos x sin 3 x
3
1 6
= sec θ tan θ
4


1 1 1
5 = (1 + cos 2 x )dx + cos 2 x sin 2 x
4 1 2 4 2 8
+ ( sec 2 θ tan θ + tan θ + C2 ) 1
5 3 3 + cos x sin 3 x
3
1 4 8 6
= sec θ tan θ + sec 2 θ tan θ + tan θ + C
4

∫ ∫
1 1 1
5 15 15 = dx + cos 2 xdx + cos 2 x sin 2 x
8 8 8
1
+ cos x sin 3 x
3
5. (a) cos(n − 1) x − cos nx cos x 6
= cos(nx − x ) − cos nx cos x x 1 1
= + sin 2 x + cos 2 x sin 2 x
= cos nx cos x + sin nx sin x − cos nx cos x 8 16 8
= sin x sin nx 1
+ cos3 x sin 3 x + C
(b) d cos m x sin nx 6
dx
= cos m x (n)cos nx
Revision Exercise 18 (p.200)
+ m cos m −1 x ( − sin x )sin nx
= n cos m x cos nx − m cos m −1 x sin x sin nx
∫ 4 3x + 7dx = ∫ (3x + 7)
1
1. 4
dx
m −1
= n cos x cos nx − m cos
m
x[cos(n − 1) x 5
− cos nx cos x ] (By (a)) (3 x + 7) 4
= +C
= n cos m x cos nx − m cos m −1 x cos(n − 1) x 3( 45 )
+ m cos m x cos nx 4 5
= (3 x + 7) 4 + C
= ( m + n)cos m x cos nx 15
− m cos m −1 x cos(n − 1) x
Chapter 18 Simple Techniques of Integration 129

∫ ∫ ∫ cos ∫
4 dx 1
= 4 (3 + 2 x ) − 2 dx
1
2. 10. 4
xdx = [ (1 + cos 2 x )]2 dx
3 + 2x 2


1 1
4( 3 + 2 x ) 2
= (1 + 2 cos 2 x + cos 2 2 x )dx
= +C 4
2( 12 )

1 1
1 = [1 + 2 cos 2 x + (1 + cos 4 x )]dx
= 4( 3 + 2 x ) 2 + C 4 2


1 3 1
= ( + 2 cos 2 x + cos 4 x )dx
4 2 2
∫ (5 sin 2 x − 6 cos 7x )dx
3 1 1
3. = x + sin 2 x + sin 4 x + C
8 4 32
5 6
=− cos 2 x − sin 7 x + C
2 7
∫ sin 2 cos 2 dx
4 x 2 x
11.

∫ [7 sin( 2 + 2) + 4 cos(4 x + 1)]dx


x
= ∫ [ (1 − cos x )]2 (1 + cos x )dx
4. 1 1
2 2
x
= ∫ (1 − cos x )(1 − cos 2 x )dx
= −14 cos( + 2) + sin( 4 x + 1) + C 1
2 8
= ∫ (1 − cos 2 x )(1 − cos x )dx
1 1
8 2
9x2 − 6x (3 x − 1)2 − 1
∫ ∫ 16 ∫
1
5. dx = dx = (1 − cos 2 x − cos x + cos x cos 2 x )dx
(3 x − 1)2 (3 x − 1)2

16 ∫
1
= ∫ [1 − (3 x − 1) −2 ]dx = [1 − cos 2 x − cos x
1 1
=x+ +C + (cos 3 x + cos x )]dx
3(3 x − 1) 2


1 1 1
= (1 − cos x − cos 2 x + cos 3 x )dx
16 2 2
8x + 8x + 9
2
2(2 x + 1) + 7
2 1 1 1 1
= x− sin x − sin 2 x + sin 3 x + C
6. ∫ 4 x 2 + 4 x + 1 dx = ∫ (2 x + 1)2 dx 16 32 32 96

= ∫ [2 + 7(2 x + 1) −2 ]dx

∫ sin x cos xdx


7 5 2
= 2x − +C 12.
2(2 x + 1)
= ∫ sin 3 x ( sin 2 x )2 dx
1
2
= ∫ sin x ⋅ (1 − cos 2 x )
1 11
∫ sin 3x cos 7xdx = 2 ∫ (sin 10 x − sin 4 x )dx
1 (1 − cos 4 x )dx
7.
2 42

16 ∫
1 1 1
=− cos 10 x + cos 4 x + C = (sin x − sin x cos 4 x − sin x cos 2 x
20 8
+ sin x cos 2 x cos 4 x )dx


1 1
= [sin x − (sin 5 x − sin 3 x )
∫ cos 2 x cos 4 xdx = 2 ∫ (cos 6 x + cos 2 x )dx
1 16 2
8.
1
− (sin 3 x − sin x )
1 1 2
= sin 6 x + sin 2 x + C
12 4 1
+ cos 2 x ⋅ (sin 5 x − sin 3 x )]dx
2


1 3 1
= [ sin x − sin 5 x
∫ sin 2 x sin 9 xdx = − 2 ∫ (cos11x − cos 7x )dx
1 16 2 2
9.
11
1 1 + (sin 7 x + sin 3 x )
=− sin 11x + sin 7 x + C 22
22 14 11
− (sin 5 x + sin x )]dx
22
130 Chapter 18 Simple Techniques of Integration

∫ [sin(5x + 4) + 3 cos 2 + 7]dx


x

1 5 1 3
= ( sin x + sin 3 x − sin 5 x 16.
16 4 4 4
= ∫ sin(5 x + 4)dx + 3∫ cos dx + 7∫ dx
1 x
+ sin 7 x )dx
4 2
5 1 3 1 x
= − cos x − cos 3 x + cos 5 x = − cos(5 x + 4) + 6 sin + 7 x + C
64 192 320 5 2
1
− cos 7 x + C
∫ (sin x − 7)dx
448 17. 2

= ∫ (1 − cos 2 x )dx − 7∫ dx
1
∫ sin x cos xdx
3 5 2
13.
= − ∫ dx − ∫ cos 2 xdx
13 1
= ∫ ( sin 2 x )3 cos 2 xdx
1
2 2
2 13 1
=− x − sin 2 x + C
= ∫ sin 2 x ⋅ (1 − cos 4 x ) (1 + cos 2 x )dx
1 1 1
2 4
8 2 2

32 ∫
1
= (sin 2 x − sin 2 x cos 4 x + sin 2 x cos 2 x
∫ (cos x − sin 7x + 2)dx
2
18.
− sin 2 x cos 4 x cos 2 x )dx
= ∫ (1 + cos 2 x )dx − ∫ sin 7 xdx + 2 ∫ dx
1

1 1
= [sin 2 x − (sin 6 x − sin 2 x )
32 2 2
= ∫ dx + ∫ cos 2 xdx − ∫ sin 7 xdx
1 1 5 1
+ sin 4 x − (sin 6 x − sin 2 x ) cos 2 x ]dx
2 2 2 2
5 1 1

1 3 1 1 = x + sin 2 x + cos 7 x + C
= [ sin 2 x + sin 4 x − sin 6 x
32 2 2 2 2 4 7
11 11
− (sin 8 x + sin 4 x ) + sin 4 x ]dx
22 22
=
1
32 2 ∫
3 1 1 1
( sin 2 x + sin 4 x − sin 6 x − sin 8 x )dx
2 2 4
19. (a)
∫ sin 3x sin xdx
= ∫ − (cos 4 x − cos 2 x )dx
1
3 1 1
=− cos 2 x − cos 4 x + cos 6 x 2
128 256 384 1 1
1 = − sin 4 x + sin 2 x + C
+ cos 8 x + C 8 4
1 024
cos 5 x − cos x
(b)
∫ sin x cos xdx
3 3 cos x
14. −2 sin 3 x sin 2 x
=
= ∫ ( sin 2 x )3 dx
1 cos x
−4 sin 3 x sin x cos x
2 =
= ∫ sin 2 x ⋅ (1 − cos 4 x )dx
1 1 cos x
8 2 = −4 sin 3 x sin x

16 ∫
1 cos 5 x − cos x
= (sin 2 x − sin 2 x cos 4 x )dx Q = −4 sin 3 x sin x
cos x
16 ∫
1 1
= [sin 2 x − (sin 6 x − sin 2 x )]dx cos 5 x
− 1 = −4 sin 3 x sin x
2 cos x
16 ∫ 2
1 3 1
= ( sin 2 x − sin 6 x )dx cos 5 x
= 1 − 4 sin 3 x sin x
2 cos x
3 1
=− cos 2 x + cos 6 x + C

cos 5 x
64 192 ∴
cos x
∫ ∫
= dx − 4 sin 3 x sin xdx
15. ∫ ∫
(cos 7 x + 9)dx = cos 7 xdx + 9 dx∫ 1 1
= x − 4( − sin 4 x + sin 2 x ) + C
8 4
1
= sin 7 x + 9 x + C 1
7 = sin 4 x − sin 2 x + x + C
2
Chapter 18 Simple Techniques of Integration 131

20. (a) sin(n − 1) x = sin nx cos x − cos nx sin x d


21. (a) (nx n −1 sin x − x n cos x )
∴ sin x cos nx = sin nx cos x − sin(n − 1) x dx
for all integer n = nx n −1 cos x + n(n − 1) x n − 2 sin x
d + x n sin x − nx n −1 cos x
cos m x cos nx
(b)
dx = x n sin x + n(n − 1) x n − 2 sin x
= cos m x ( − sin nx )(n) (b) By (a),
+ m cos m −1 x ( − sin x )cos nx nx n −1 sin x − x n cos x
m −1
= − n cos x sin nx − m cos
m
∫x ∫
x sin x cos nx
m −1
= n
sin xdx + n(n − 1) x n − 2 sin xdx
= − n cos x sin nx − m cos
m
x sin nx cos x
m −1
∫x
n
+ m cos x sin(n − 1) x sin xdx
m −1
= m cos x sin(n − 1) x = nx n −1 sin x − x n cos x
− ( m + n)cos x sin nx for any integer m ≥ 2
m

(c) By the result of (b), for any integer n ≥ 2 ,



− n(n − 1) x n − 2 sin xdx
In = nx n −1 sin x − x n cos x − n(n − 1) In − 2
cos m x cos nx
∫x
4
(c) sin xdx

m −1
= m cos x sin(n − 1) xdx
= I4


− ( m + n) cos x sin nxdx = 4 x 3 sin x − x 4 cos x − 4(3) I2
m

= 4 x 3 sin x − x 4 cos x
∫ cos
m
x sin nxdx − 12[2 x sin x − x 2 cos x − 2(1) I0 ]


m = 4 x 3 sin x − x 4 cos x − 24 x sin x
= cos m −1 x sin(n − 1) xdx
m+n

1
cos m x cos nx

+ 12 x 2 cos x + 24 sin xdx
m+n = − x 4 cos x + 4 x 3 sin x + 12 x 2 cos x
When m = n , −24 x sin x − 24 cos x + C

∫ cos x sin nxdx


n
d
22. (a) x ( x 2 + 1) n
= ∫ cos n −1 x sin(n − 1) xdx
1 dx
2 = xn( x 2 + 1) n −1 (2 x ) + ( x 2 + 1) n
cos n x cos nx = ( x 2 + 1) n −1[2 nx 2 + ( x 2 + 1)]

= ( x 2 + 1) n −1[(2 n + 1)( x 2 + 1) − 2 n]
2n

= (2 n + 1)( x 2 + 1) n − 2 n( x 2 + 1) n −1
∫ cos x sin 3xdx
3
(d)
cos3 x cos 3 x (b) By (a),
= ∫ cos 2 x sin 2 xdx −
1
2 6 x ( x 2 + 1) n
2
∫ ∫ ∫
1 1 cos x cos 2 x
= ( cos x sin xdx − ) = (2 n + 1) ( x 2 + 1) n dx − 2 n ( x 2 + 1) n −1 dx
2 2 4
cos3 x cos 3 x

6 ∫
(2 n + 1) ( x 2 + 1) n dx

=
1 1

sin 2 xdx −
cos 2 x cos 2 x ∫
= 2 n ( x 2 + 1) n −1 dx + x ( x 2 + 1) n
4 2 8
∫ (x + 1) n dx
2
cos3 x cos 3 x

6 x ( x 2 + 1) n

2n
1 1 = ( x 2 + 1) n −1 dx +
= − cos 2 x − cos 2 x cos 2 x 2n + 1 2n + 1
16 8
1 2n x ( x 2 + 1) n
− cos x cos 3 x + C
3 In = In −1 +
6 2n + 1 2n + 1
132 Chapter 18 Simple Techniques of Integration

x3 dy d n −1
= sin x 2

(b) x
(c) (i) I1 = ( x 2 + 1)dx = + x + C1 dx dx
3
= x n −1 ⋅ 2 x cos x 2 + (n − 1) x n − 2 sin x 2
∫ (x + 1)3 dx = 2 x n cos x 2 + (n − 1) x n − 2 sin x 2
2
(ii)
= I3 dz
=
d n −1
x cos x 2
6 x ( x + 1)
2 3 dx dx
= I2 + = x n −1 ( −2 x sin x 2 ) + (n − 1) n − 2 cos x 2
7 7
6 4 x ( x 2 + 1)2 x ( x 2 + 1)3 = (n − 1) x n − 2 cos x 2 − 2 x n sin x 2
= [ I1 + ]+
7 5 5 7
(c) By the results of (b), for any integer n ≥ 2 ,
24 x 3 6 x ( x 2 + 1)2
= ( + x + C1 ) +
35 3
x ( x 2 + 1)3
35

x n −1 cos x 2 = (n − 1) x n − 2 cos x 2 dx
+
7 ∫
− 2 x n sin x 2 dx
x ( x 2 + 1)3

1
x sin x dx = − x n −1 cos x 2
8 3 24 n 2
= x + x+
35 35 7 2
n − 1 n−2
+
6 x ( x 2 + 1)2
+C
+
2
x ∫
cos x 2 dx
35
1 n −1 n −1
∴ Sn = − x cos x 2 + Cn − 2
2 2


Enrichment 18 (p.201)
x n −1 sin x 2 = 2 x n cos x 2 dx
1. (a) sin 3θ = sin(2θ + θ)
= sin 2θ cos θ + cos 2θ sin θ ∫
+ (n − 1) x n − 2 sin x 2 dx

= 2 sin θ cos θ + (1 − 2 sin θ)sin θ


2 2
∫x
1
n
cos x 2 dx = x n −1 sin x 2
= 2 sin θ(1 − sin θ) + sin θ − 2 sin θ
2 3 2
n − 1 n−2
= 3 sin θ − 4 sin 3 θ −
2
x ∫
sin x 2 dx

1 n −1
(b)
sin 3θ 3 sin θ − 4 sin 3 θ
= ∴ Cn = x n −1 sin x 2 − Sn − 2
sin θ sin θ 2 2
= 3 − 4 sin 2 θ
∫x
3
(d) (i) sin x 2 dx
sin 3θ = S3

∫ sin θ ∫ ∫
= 3 dθ − 4 sin 2 θdθ
1
= − x 2 cos x 2 + C1
= 3∫ dθ − 4 ∫ (1 − cos 2θ)dθ
1 2
2

1
= − x 2 cos x 2 + x cos x 2 dx
= ∫ dθ + 2 ∫ cos 2θdθ 2
= θ + sin 2θ + C =−
1 2 1
x cos x 2 + sin x 2 + C (By (a)(ii))
2 2

∫x
3
2. (a)
d
sin x 2 = 2 x cos x 2
(ii) cos x 2 dx
dx = C3
d
cos x 2 = −2 x sin x 2 1
dx = x 2 sin x 2 − S1
2


1
∫ x sin x
1
(i) 2
dx = − cos x 2 + C = x 2 sin x 2 − x sin x 2 dx
2 2
1 2 1
= x sin x 2 + cos x 2 + C (By (a)(i))

1
(ii) x cos x 2 dx = sin x 2 + C 2 2
2
Chapter 18 Simple Techniques of Integration 133

3. (a) For any integer n ≥ 2 , Classwork 1 (p.192)


d x2 + 1 ( 3 x + 2 ) 5 +1
dx x n −1 1.
∫ (3 x + 2)5 dx =
3(5 + 1)
+C
1 1
= [ x n −1 (2 x ) − (n − 1) x n − 2 (3 x + 2 ) 6
2 x +1
2 = +C
18
x 2 + 1 ] ÷ ( x n −1 )2
− (n − 1) x n − 2 x 2 + 1
∫ ∫
dx
xn
= (1 − 2 x ) − 2 dx
1
2.
= x 2 +1 1 − 2x
2n − 2
(1 − 2 x ) − 2 +1
1
x
= +C
1 x2 + 1 −2( − 12 + 1)
= + (1 − n)
x n−2 x 2 + 1 xn = − 1 − 2x + C
1 x2 + 1
= + (1 − n)
x n−2 x 2 + 1 xn x2 + 1 x2 − 4x ( x − 2)2 − 4
=
1 3.
∫ x2 − 4x + 4
dx = ∫ ( x − 2)2
dx
n−2
x +1
2

x 4
1 1 = [1 − ]dx
+ (1 − n)[ + ] ( x − 2)2
n−2
x +12 n
x2 + 1
∫ ∫
x x 4 dx
= dx −
( x − 2)2
∫ xn
dx
(b) Let In = , therefore, by the result
x2 + 1 = ∫ dx − 4 ∫ ( x − 2) −2 dx
of (a), for any integer n ≥ 2 , ( x − 2) −2 +1
= x−4 +C
−2 + 1
x2 + 1
∫ x n−2
dx
= + (1 − n) =x+
4
+C
x n −1 x2 + 1 x−2

∫ x n−2 ∫ xn
dx dx
[ + ]
x +1 2
x2 + 1
∫ sin 7xdx = −
cos 7 x
= In − 2 + (1 − n)( In − 2 + In ) 4. +C
7
= (2 − n) In − 2 + (1 − n) In

sin(3 x + 7)
∴ In =
x2 + 1
n −1
+
n−2
1− n
In − 2
5. ∫ cos(3x + 7)dx = 3
+C
(1 − n) x

∫ x2
dx
(c) (i) = I2 Classwork 2 (p.194)
x2 + 1
x2 + 1
∫ sin 2 x cos 2 xdx = ∫
sin 4 x
= + C1 1. dx
−x 2
1 − cos 4 x
= ( )+C
∫ x4
dx
(ii) 2 4
1 + x2 1
= − cos 4 x + C
= I4 8
x2 + 1 2
= + I2
∫ sin 2 x sin 3xdx = ∫ − 2 [cos 5x − cos(− x )]dx
(1 − 4) x 3 −3 1
2.
x2 + 1 2 x2 + 1
= − ∫ cos 5 xdx + ∫ cos xdx
=− − ( − ) + C2 1 1
3x 3 3 x 2 2
x2 + 1 2 x2 + 1 1 sin 5 x 1
=− + + C2 =− + sin x + C
2 5 2
3x 3 3x
1 1
= − sin 5 x + sin x + C
10 2
134 Chapter 18 Simple Techniques of Integration

nIn = (n − 1) In − 2 − sin n −1 θ cos θ


∫ sin ∫ 2 (1 − cos 2 x )dx
1
3. 2
xdx =
n −1 1
= ∫ dx − ∫ cos 2 xdx
1 1 ∴ In = In − 2 − sin n −1 θ cos θ
2 2 n n
1 1 sin 2 x
= x− +C
2
1
2 2
1
(c) (i) ∫
I1 = sin θdθ = − cos θ + C1
= x − sin 2 x + C 1 1
2 4 I2 = I0 − sin θ cos θ
2 2
1 1
= θ − sin θ cos θ + C2
Classwork 3 (p.196) 2 2

∫ sin x cos xdx ∫ sin θdθ


2 3 (ii) 3
1.
= I3
sin 2 2 x
=∫ cos xdx 2 1
4 = I1 − sin 2 θ cos θ
3 3
= ∫ sin 2 x[ (sin 3 x + sin x )] dx
1 1
2 1
4 2 = − cos θ − sin 2 θ cos θ + C
3 3
= ∫ [ − (cos 5 x − cos x ) − (cos 3 x − cos x )] dx
1 1 1
8 2 2
∫ sin θdθ
4
= − ∫ (cos 5 x + cos 3 x − 2 cos x )dx
1
16 = I4
= − ∫ cos 5 xdx − ∫ cos 3 xdx + ∫ cos xdx
1 1 1 3 1
16 16 8 = I2 − sin 3 θ cos θ
4 4
sin 5 x sin 3 x sin x 3θ 3
=− − + +C =
1
− sin θ cos θ − sin 3 θ cos θ + C
80 48 8 8 8 4

∫ (1 + sin x ) dx
2
2.

= ∫ (1 + 2 sin x + sin 2 x )dx

= ∫ dx + 2 ∫ sin xdx + ∫ (1 − cos 2 x )dx


1
2
= ∫ dx + 2 ∫ sin xdx + ∫ dx − ∫ cos 2 xdx
1 1
2 2
3x 1
= − 2 cos x − sin 2 x + C
2 4

Classwork 4 (p.198)
(a) For any integer n ≥ 2 ,
d
sin n −1 θ cos θ

= (n − 1)sin n − 2 θ cos 2 θ + sin n −1 θ( − sin θ)
= (n − 1)sin n − 2 θ(1 − sin 2 θ) − sin n θ
= (n − 1)sin n − 2 θ − n sin n θ

(b) By the result of (a), for any integer n ≥ 2 ,

sin n −1 θ cos θ

∫ ∫
= (n − 1) sin n − 2 θdθ − n sin n θdθ
= (n − 1) In − 2 − nIn